Effects of different parenting styles on the physical health of Chinese university students - Liu, Minghao; Li, Jingping; Chang, Sai; Liang, Yi; Wang, Zheng (Frontiers in Public Health, 2024)
Annual declines in university students' physical health have an impact on social stability and the nation's long-term growth. Parenting style, which is crucial to a child's growth and development, may have a big influence on physical health. This study delves into the effects of different parenting styles on the physical fitness of Chinese college students under gender differences.Methods: Through random allocation and stratified sampling methods, this study comprehensively investigated 3,151 undergraduate students (male = 1365; female = 1786) with an average age of 18.44 years (SD = 1.46), from a university in Jiangsu Province, China. Parenting styles of college students were evaluated by the Parental Bonding Instrument (PBI). Physical fitness tests were based on the Chinese National Student Physical Fitness Standards including body mass index, lung capacity, standing-long-jump, bent-leg-sit-up, seated forward bend, pull-ups, 50 m sprint, and 800/1,000 m run. Further investigations focused on the relationship between parenting styles and physical health by statistical analysis methods such as Pearson correlation and multiple linear regression.Results: Significant differences were identified in gender, family members, and academic majors in most of the correlation indicators between different parenting styles and physical health among college students. Further analysis showed that the parenting styles of democratic and authoritative mothers and democratic fathers were more conducive to the promotion of physical health among female university students. The combination of a democratic fathering style and a permissive mothering style is considered an ideal parenting model for male students.This study confirmed that different parenting styles have a significant impact on the physical health of college students. Positive parenting styles may improve physical health, while negative ones are likely to have adverse effects, especially among female students. It is also important to notice differentiated parenting styles with respect to male and female university students. Therefore, more attention should be raised on parenting styles to enhance physical health of the student population.